Perbandingan Model Pembelajaran Kooperatif Tipe Student TeamsAchievements Divisions (STAD) dan Course Review Horay (CRH) Terhadap Hasil Belajar Siswa pada Mata Pelajaran Sejarah Kelas XI IPS SMA N 1 Gunung Talang - Veryola Malvy; Zafri Zafri (Jurnal Kronologi, 2019)
This research is motivated by the initial findings of researchers related to the low student learning outcomes and the weaknesses of the learning model applied by history subject teachers at SMA N 1 Gunung Talang, this is seen from the lack of mastery of student material. That is caused by the learning methods used by teachers are less effective. This study aims to determine whether there are differences in learning outcomes of the two learning models applied to different classes, namely the Student Teams-Achievement Achievement Division (STAD) and Course Review Horay (CRH) learning models on history subjects at SMA N 1 Gunung Talang. This study used an experimental method with a postest only control design. The population in this study were students of Class XI of SMA N 1 Gunung Talang, the sample of this study was Class XI IPS 3 as an STAD class I and Class XI IPS 4 as an CRH class. Data collection was carried out by means of posttest using 13 items of objective questions. Data analysis using normality test, homogeneity test, and hypothesis testing (t test)). Based on the results of the study, the STAD class grade score obtained by the Student Teams-Achievements Division (STAD) learning model was 78,96 with a standard deviation of 13,88 and the average in the CRH class with the Course Review Horay (CRH) learning model was 70,52 with a standard deviation of 16,68. Based on the results of hypothesis testing using t-test (t-test) at the real level α = 0.05, obtained tcount = 2,19 and ttable = 2,000 so tcount> ttable, then the Ha hypothesis in this study was accepted and rejected Ho. It can be concluded that the learning model of Student Tem-Achievements Division (STAD) and Course Review Horay (CRH) influences student learning outcomes and mastery of student material in history subjects at SMA N 1 Gunung Talang in the 2019/2020 school year